Ніжинський грецький суд і магістрат у ХУІІ – ХУІІІ ст. - Пилипенко, Олександр Євгенійович (My University, 2018)
Наукова стаття присвячена діяльності Ніжинського грецького суду та магістрату. Вивчено основні напрямки діяльності магістрату ніжинських греків, його значення для життя громади. Досліджено правову базу функціонування Ніжинського грецького братства та його юридичний статус. Детально проаналізовано основні справи, які розглядав та вирішував магістрат, визначено його компетенцію і співпрацю з іншими магістратами Російської імперії. Окреслено подальші напрямки дослідження даної теми. The scientific article is devoted to activity of the Nizhin Greek Court and Magistrate. The main directions of activity of the Nizhin Greeks Magistrate, it value for life of brotherhood are studied. The legal status and law base of function of Nizhin Greek merchants brotherhood in the territory of Ukraine are investigated. Many cases was anylysed by state were determine, his competence and cooperation with other magistrate of the Russian Empire. Further of researching of this topic are outlined. The Greek Nizhin court played an important role in life of the Greek migrants. Exactly the newly arrived Greeks trusted consideration of commercial and civil businesses him. He got the name of «mediation court» yet. Because judge mediator that was appointed from a number the most worthy, authoritative and experience Greek merchants. In course of time in city Nizhin there was own the Greek city magistrate (council) carried out the activity next to the Nizhin municipal city council. But unlike the last, he decided business exceptionally of citizen foreigners. The Nezhin city Greek magistrate became an original center that joined Greeks and other foreign migrants in Ukraine. Many business that was examined a city council were saved in the archive documents. Mainly these were criminal, civil, commercial, administrative cases. It was not accepted to appeal the decitions of Greek magistrate and cases of appeals were single. Activity of members of the Nizhin Greek magistrate used large respect and honour of fellow-citizens. Nizhin Greek magistrate was activity until 1868 year.
Keywords: суд; магистрат; Ніжинське грецьке братство; інструкції; справи; рішення; ухвали; кафедра гуманітарних дисциплін; court; magistrate; greek brotherhood; kases; instructions; decrees; decisions